Pension Design with a Large Informal Labor Market: Evidence from Chile - Clement Joubert (Institute for the Study of Labor (IZA), 2014)
This paper investigates empirically the fiscal and welfare trade-offs involved in designing a pension system when workers can avoid participation by working informally. A dynamic behavioral model captures a household's labor supply, formal/informal sector choice and saving decisions under the rules of Chile's canonical privatized pension system. The parameters governing household preferences and earnings opportunities in the formal and the informal sector are jointly estimated using a longitudinal survey linked with administrative data from the pension system's regulatory agency. The parameter estimates imply that formal jobs rationing is limited and that mandatory pension contributions play an sizeable role in encouraging informality. Our policy experiments show that Chile could achieve a reduction of 23% of minimum pension costs, while guaranteeing the same level of income in retirement, by increasing the rate at which the benefits taper off.
Keywords: J24; J26; E21; E26; O17; 330; informality; pensions